Enhancing person-centred care in inpatient mental health settings through supported person-side handover: a multi method study. Issue 3 (4th July 2021) - Paul, Diane; Glover, Suzanne; Roche, Michael Anthony; Klarnett, Karen; Chen, Xiaomeng; Wall, James; Joyce, Mark
Abstract : Background: Many nursing contexts have introduced bedside handover, where the person in care participates in the transfer of clinical information, with benefits for person, carers, and clinicians. This type of handover has been implemented across a number of mental health settings, but there is limited evidence regarding implementation approaches or of practice change. This study reports the development and evaluation of a co-produced education and support package. Aim: To evaluate changes in nurses' practice regarding bedside (person-side) handover following implementation of a structured education and support package. Design: Multi-method design incorporating nurse surveys and chart audit. Methods: The survey and audit were conducted in 2019–2020 on two inpatient mental health units in a metropolitan health service immediately prior to, and 6 months after, implementation, with 70 survey responses and 52 files audited. Non-parametric tests assessed change, and text comments were reported. Results: Significant improvements were observed in nurses' reports of confidence, the ability to maintain privacy, identified benefits for the person and in information transfer. In contrast, the chart audit identified no change in documentation of this practice. Conclusions: The implementation of a co-produced education and support package demonstrated positive practice change in engaging people receiving care in handover. This approach to handover provides increased opportunity for nurses to work in partnership with people receiving mental healthcare, facilitating collaborative person-centred care and shared decision making.